Pituitary-gonadal control of creatinine metabolism. - Cheetham, Richard William Spencer (Division of Physiological Sciences, 2020)
The endocrine in general for a considerable period have been known to exert a humoraal action on the body, controlling its functions to a large extent. These actions have been closely investigated and a clear correlation between the ductless glands have been shown. The interrelation and dependency of the one upon the other, either by inhibition or by stimulation, contribute towards the finer control of the physiology of the body. The studies recorded here are comprised mainly of the dependency of one gland upon another, the relation the normal gland has to protein metabolism, and the alteration in this protein metabolism brought about by alteration in the normal function of one or other of the ductless glands. These features are demonstrated by observing changes in the elimination of creatinine in urine, for this urinary creatinine is regarded as an index of endogenous protein metabolism, and the amount excreted is remarkably constant from day to day.